Between emergency precautionary measures and the substantial resolution of conflicts that generate complaints for intra-family violence: An experience of joint judicial action for access to justice and timely judicial protection - Rimachi Huaripaucar, Hugo (2023)
The increase in the rates of complaints for intrafamily violence is a reflection of the levels of conflict among those who make it up, the most affected part being the children, who in turn become the reason for disputes between the parents over their possession, visits and food, generating acts of violence between parents that have repercussions on the children, in view of which, it is the role of judges to proactively assume the issuance not only of the protection measures provided by law, but also of precautionary measures on those points in dispute and that should be resolved on the merits with the urgency of the case and with the guarantees of due process before the competent court. The experience that is shared is framed within that purpose of guaranteeing in the best way the protection of victims, access to justice and the cessation of violence.